Flood Risk Pattern Recognition Using Chemometric Techniques Approach in Golok River, Kelantan - Nur Amyliyana Wan Faizurie Zaidee, Wan; Shakir Mohd Saudi, Ahmad; Khairul Amri Kamarudin, Mohd; Ekhwan Toriman, Mohd; Juahir, Hafizan; Fahmy Abu, Izuddin; Mahmud Nur Zahidah Shafii, Muaz; Nizam, Khairul; Elfithri, Rahmah (International Journal of Engineering and Technology, 2018)
This study was implemented to evaluate the flood risk pattern recognition in Golok River, Kelantan. Based on Spearman correlation test, it showed that water level and suspended solid was very strong and significant (p < 0.0001). There was also a weak correlation of coefficient of stream flow and rainfall with the changes of water level as the p-value close to 1. Suspended solid has strong corresponded in changing the rate of water level, as it described the rate of surface run-off that flowed into the water body. However, the risk of flood in study area is irrelevant to the monsoon season. Principle Component Analysis (PCA), the most sensitive parameters that contribute to the flood occurrence were identified with variability R2 value of 0.812 and 0.764. Expansion and development by human activities contribute to the incline of stream flow and suspended solid in Golok River. Based on Statistical Process Control (SPC), water level of all parameters exceeded the Upper Control Limit (UCL), considered as high risk and vulnerable for flood and it is mostly due to man-made activities. It was not deniable that monsoon season played role in contributing flood occurrence as parameters of rainfall and water level have moderately positive factor loading.Â Â